Pitch woman and other stories : the oral traditions of Coquelle Thompson, Upper Coquille Athabaskan Indian - Thompson, Coquelle, 1848-1946 (Native literatures of the Americas., 2007)
The rich oral traditions of the Athabaskan Indians from southwestern Oregon are showcased in these pages for the first time. This volume features vivid and humorous tales of familiar Tricksters: Coyote, known for his unusual sexual prowess and escapades that often go awry; the vain and gullible Grizzly Bear; and Raccoon, often greedy and ever elusive. The collection also includes the less familiar but all-too-human stories of Pitch Woman, Little Man, the unicorn-like Hollering-Like-a-Person, and other local figures, all of which add to the wealth of Native oral literature in the Pacific Northwest.